Sensitivity and Specificity of Rapid Diagnostic Test with Microscopic Gold Standard to Identify Plasmodium Species - Sahrir Sillehu; Heny Arwati; Yoes Prijatna Dachlan; Sudjajadi Keman (Intelektual Pustaka Media Utama, 2016)
Malaria is a main health problem in islands area which is under developed and isolated. Nation-wide, in 2014 Maluku province was recorded to have Annual Malaria Incident (AMI) value of 30.4%, positive incidents of 13.30%, ABER 3.76%, SPR 21.50%, and Annual Paracite Incident (API) 8.10%, while South Buru Regency has a value of Annual Malaria Incident (AMI) of 14.49%, 494 positive incidents, ABER 1.12%, SPR 60.91%, and Annual Paracite Incident (API) 6.86%. The purpose of this study was to identify Plasmodium species in malaria incidents in NamroleSubdistrict, South Buru Regency, Maluku Province. Observational research with a sample of 64 respondents for symptomatic and asymptomatic malaria. The instrument for the research was Rapid Diagnostic Test (RDT) and microscopic Gold Standard. Result: Malaria examination by using RDT suggested 3 kinds of parasites, i.e., P. falciparum, P. Vivax, and a mix between P. falciparum and P. vivax. Most parasites found were P. falciparum 56.3%. The accuracy of RDT examination was proven with microscopic test and the result suggested that the RDT sensitivity was 100% and the specifivity was 63.3%. Positive predictive value was 92.9% and negative predictive value was 100%, both were for positive likelihood ration of 2.75%. While for negative likelihood ration of 0%, the value of degree of conformity (Kappa) between RDT and microscopic is 0%. RDT has one benefit that it can be use to conduct malaria diagnosis rapidly, particularly in isolated areas. The benefit of Rapid Diagnostic Test (RDT) was that it could be used in remote and isolated areas to conduct diagnosis. RDT is highly effective and efficient.